Situation Report: Bulgaria, 1 April 1965 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Interview with the Minister of Finance Bulgaria Buys Chemical Plant from Krupp Zhivkov Received East German Ambassador End of Raul Castro's Visit Support for Vietnam Reaffirmed New Trade Agreement with Britain